Information security of modern business organizations - Kurdulian Victoriia; Kucheriavy Evheniy; Denisenko Nataliia (Закарпатський угорський інститут імені Ференца Ракоці II, 2024)
Abstract. The relevance of business information security is an integral component in today's world. The development of information technologies allows businesses to earn significant benefits by accelerating efficiency and improving the management of various processes. Confidential data, creative activity and customer information are some of the most valuable data. Large companies are attacked dozens of times a day, while cybercriminals constantly scan the information security perimeter and monitor vulnerabilities. That's why companies should prioritize cybersecurity to protect their information, maintain customer trust, and not lose their reputation. First, let's consider the concept of cyber security. Cybersecurity is a term that describes the set of methods and procedures used by businesses and IT professionals to ensure an adequate level of protection of an organization's confidential electronic data and digital systems from unauthorized intervention and theft for the purpose of extortion, blackmail and business damage. Most commonly, cybercriminals use tactics such as phishing attacks, malware, and social engineering to compromise systems and steal data. They look for software vulnerabilities, misconfigurations, and human error as entry points.
Keywords: information security; business; cyber security; Artificial Intelligence